Strategic Drivers of Growing Indo-GCC Relations - Asia Karim; Amna Mahmood, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
Owing to its geo-strategic location and being rich in hydrocarbons, Gulf region holds a lot of significance for India. Historically Indo-Gulf relations were primarily focused on economic basis with India being the receiver of Gulf oil and the exporter of human capital to the labour intensive Gulf market which later gradually transformed into strategic partnerships. The contemporary era is marked by increased Indo-Gulf cooperation. Economic interdependence, enhanced political understanding and growing security cooperation are the hallmark of this cooperation. Study aims to probe out historical evolution of Indo-Gulf ties. These relations are studied under the theoretical paradigm of complex interdependence. It is mainly addressing the research question: What are the major strategic drivers of growing Indo-Gulf cooperation? For addressing this question qualitative research method is used. Data is randomly chosen from different research papers and books. For primary data reports from ministry of external affairs, India are extracted. The research concludes that energy security, security of Sea Lanes of Communications (SLC), Indian diaspora, huge commercial markets and new generation of leaders in Gulf region are primary drives behind enhanced Indo-Gulf cooperation.